Bioethics of Bioastronautics - Profitiliotis (Γεώργιος Προφητηλιώτης) George (Bioethica, 2020)
The rise of emergent space initiatives -especially of private ones- has begun to push the boundaries of the space industry, thanks to technological innovations that will soon be able to significantly facilitate the development of previously neglected pioneering fields, such as, for example, space research and exploration, space resources utilization, and human access to space. The invigoration and the forthcoming growth of this new space economy in the aforementioned pioneering fields are expected to bring forward important bioethical issues. The purpose of this paper is to summarize the most important of these issues, after a review of a significant number of relevant publications in the international academic literature. In particular, this paper will present bioethical issues in the field of bioastronautics -especially in light of future missions to Mars- that refer to both life on Earth, i.e. microorganisms, plants, animals and humans, and to potential extraterrestrial life. Given the accelerating rate of developments, the best time to discuss these issues, in order to inform policymaking, is now.